Homage to Konstanze Vernon Hans-Theodor Wohlfahrt at the Bavarian State Opera in Munich - Wohlfahrt, Hans-Theodor (Dance Books Ltd., Alton,Hampshire (UK), 1998)
PALABRAS CLAVE: Bavarian National Ballet, Konstanze Vernon, life and career.